Comparison of Examination Results of Acid-Fast Bacilli (AFB) Ziehl Neelsen (ZN) Method on BTA Preparations that are Directly Stained with Delayed Preparations - Asni Hasanuddin; Rony Setianto; Belinda Arbitya Dewi (Nusantara Scientific Medical, 2022)
Tuberculosis is a direct infectious disease caused by the bacterium Mycobacterium tuberculosis. Most tuberculosis germs attack the lungs, which is known as Pulmonary Tuberculosis (pulmonary TB), but can also affect other organs, which is called extrapulmonary TB. Pulmonary TB germs in the form of rods, have special properties, namely acid resistance to staining. The purpose of this study was to determine the results of examination of acid fast bacilli (AFB) by the Ziehl Neelsen method on smear preparations which were immediately stained and left to stand for three days. The research was conducted using a descriptive approach with a sample of 10 people using a purposive sampling technique. In this study, staining was carried out twice, namely direct staining and delayed staining for 3 days and examined under a microscope. The results showed that there was no difference between the preparedness that was immediately colored and the one that was postponed for three days.